De Novo Missense Variant in Bovine WDR33 Associated With a Complex Syndromic Form of Cleft Palate With Pentalogy of Fallot and Internal Hydrocephalus - Marilena Bolcato; Giovanni Romito; Irene M. Häfliger; Arcangelo Gentile; Cord Drögemüller; Joana G. P. Jacinto (Journal of Veterinary Internal Medicine, 2025)
ABSTRACT Background Cleft palate (CP) is a congenital defect characterized by an opening in the palate. Two crossbred paternal half‐sibs with a complex syndrome including CP were identified. Hypothesis/Objectives Characterize disease phenotype and evaluate the genetic cause of the observed syndrome. Animals Two affected calves, their parents, and 5576 control cattle genomes. Methods The affected animals were evaluated clinicopathologically. Paternal half‐sibling trio‐based whole genome sequencing (WGS) was performed using genomic DNA extracted from the blood of the two affected calves and both dams, and sperm of the common sire. Results The cases were presented with a CP Veau II, permanent recumbency, strabismus, tachycardia, and tachypnea. Echocardiographic findings were consistent with tetralogy of Fallot associated with patent foramen ovale (pentalogy of Fallot). Necropsy examination identified hydrocephalus in addition to CP and confirmed the clinical diagnosis of pentalogy of Fallot. The calves were diagnosed with a complex syndromic form of CP with pentalogy of Fallot and hydrocephalus. Analysis of the breeding data showed that 19/45 recorded offspring of the sire were not viable. Genetic analysis identified a missense variant in WDR33 that was heterozygous in both analyzed cases and in an estimated 40% of the paternal gametes of the mosaic founder, but absent in both dams and controls. Conclusions and Clinical Importance This study alerts veterinarians and breeders to the potential occurrence of dominant de novo mutations in cattle and emphasizes that, in herds using a natural service sire, the consequences of an asymptomatic germline mosaic can be important.